(Invited) Plasma-Enhanced Quasi-ALE and ALD Processing for Leading-Edge Microfabrication. (16th August 2016) - Honda, Masanobu; Katsunuma, Takayuki; Tabata, Masahiro; Tsuji, Akihiro; Oishi, Tomoyuki; Hisamatsu, Toru; Ogawa, Shuhei; Kihara, Yoshihide
Abstract : We introduce a state-of-the-art self-aligned contact (SAC) process and patterning process developed by new patterning technology using Atomic Layer Etch (ALE) and Atomic Layer Deposition (ALD) towards 5/7nm generation. SAC process is known to require SiO2 etching capability with ultra-high selectivity to SiN. We developed Quasi-ALE technique to improve ALE process to make it more suitable for SiO2 Etch. By adopting this technology to SAC process, the conventional trade-offs between fine process control and SiO2 selectivity to SiN in the fine slit pattern is significantly improved. On the other hand, in the patterning process, CD shrink technique without CD loading is one of the key requirements. By integrating ALD process into the etching flow, we developed a process that can control the CD shrink amount in the atomic layer level without causing CD loading.